2011
DOI: 10.1038/clpt.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Metabolite Concentrations, CYP2D6 Genotype, and Breast Cancer Outcomes

Abstract: We explored whether breast cancer outcomes are associated with endoxifen and other metabolites of tamoxifen, and to examine potential correlates of endoxifen concentrations including CYP2D6 metabolizer phenotype and body mass index (BMI). Tamoxifen, endoxifen, 4-hydroxytamoxifen and N-desmethyltamoxifen concentrations were measured from 1370 estrogen receptor positive breast cancer patients participating in the Women's Healthy Eating and Living (WHEL) Study, and tested for associations with breast cancer outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
407
4
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(456 citation statements)
references
References 26 publications
22
407
4
8
Order By: Relevance
“…On the other hand, however, in premenopausal patients, the potential benefit from prolonged use of TAM should be interpreted with caution, as this group of patients made up only 13% of the total number of patients treated within the studies comparing varied periods of using TAM [15][16][17]. Irrespective of individual differences in the pharmacokinetics of TAM, about 20% of patients treated with this medication did not reach the treatment threshold of endoxifen -its main active metabolite [18][19][20].…”
Section: Ovarian Function Suppression In Tamoxifen Therapymentioning
confidence: 99%
“…On the other hand, however, in premenopausal patients, the potential benefit from prolonged use of TAM should be interpreted with caution, as this group of patients made up only 13% of the total number of patients treated within the studies comparing varied periods of using TAM [15][16][17]. Irrespective of individual differences in the pharmacokinetics of TAM, about 20% of patients treated with this medication did not reach the treatment threshold of endoxifen -its main active metabolite [18][19][20].…”
Section: Ovarian Function Suppression In Tamoxifen Therapymentioning
confidence: 99%
“…Было показано, что у IMs и PMs концентрация эндоксифена была ниже на 60 и 74 %, чем у EMs. Ген-дозазависимый эффект также проде-монстрирован для тамоксифена и соотношения мета-болитов N-дисметилтамоксифен / эндоксифен [35][36][37].…”
Section: Introductionunclassified
“…CYP2D6 activity is highly associated with TAM metabolism and may affect clinical activity. 11,12 Coincubation of TAM with potent, specific CYP2D6 chemical inhibitors such as quinidine and the antidepressant paroxetine confirmed that the inhibition of CYP2D6 activity prevents the formation of the important metabolite endoxifen. However, because TOR is less subject to CYP2D6-mediated hydroxylation, these inhibitors had little effect on the metabolism of TOR in our assays.…”
mentioning
confidence: 99%
“…1). [10][11][12] These metabolites bind to the ER with up to 30-fold greater affinity than TAM, and this increased potency for binding translates into enhanced antiestrogen activity. …”
mentioning
confidence: 99%
See 1 more Smart Citation